Hubungan Disiplin Kerja dengan Kinerja Pegawai pada Kantor Desa Kemboja di Kecamatan Pulau Maya Kabupaten Kayong Utara - Muliana, Pitania; Firayanti, Yuni; Mahardhika, Tubagus (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the relationship between work discipline and employee performance at the Kemboja Village Office, Pulau Maya District, Kayong Utara Regency. Work discipline is an important factor in improving employee performance, which includes aspects of attendance, compliance with regulations, responsibility, and compliance with work standards. The research method used is quantitative with a correlational approach. Data was collected through a questionnaire distributed to 96 respondents who are residents of Kemboja Village, with a sampling technique using the Slovin formula. The results showed that there was a positive and significant relationship between work discipline and employee performance, with a correlation coefficient of 0.849 and the contribution of work discipline to employee performance of 72.1%. Simple linear regression analysis yielded an equation of Y=2.733+0.895X, which showed that any increase in work discipline would increase employee performance by 0.895 points. The hypothesis test with the t-test also confirmed that work discipline has a significant effect on employee performance (t count 15.589 > t table 1.9855). This finding shows that the higher the work discipline, the better the employee's performance in providing services to the community.